Use of alcohol swabs to clean injecting sites among people who regularly inject drugs in Australia. (11th December 2019) - Gibbs, Daisy; Peacock, Amy; O'Keefe, Daniel; Butler, Kerryn; Bruno, Raimondo; Lenton, Simon; Burns, Lucinda; Larney, Sarah
Abstract: Introduction and Aims: Cleaning drug injection sites with alcohol swabs prior to injecting reduces risk of abscesses and other skin and soft tissue infections (SSTI). Better understanding of swabbing behaviours can inform interventions to improve injecting hygiene. We aimed to determine the socio‐demographic, drug use and injecting risk exposure correlates of swabbing prior to injecting and reasons for not swabbing. Design and Methods: The Illicit Drug Reporting System recruited participants who had injected drugs at least monthly in the past six months in June–July 2017 from all Australian capital cities via needle and syringe programs and word‐of‐mouth. A structured interview was used to collect information on drug use and related behaviour, as well as swabbing practices. Logistic regression was used to identify factors associated with not swabbing at last injection. Results: Of 853 respondents, one‐quarter (26%) reported that they did not swab prior to their last injection. In adjusted analyses, crystal methamphetamine as the last drug injected, past month receptive or distributive syringe sharing, and past month re‐use of one's own needle were significantly associated with not swabbing at last injection. Among participants who did not swab at last injection, swabbing was frequently considered unnecessary and a small number disliked using alcohol swabs. Discussion and Conclusions: Efforts are needed to increase awareness of the importance of injecting hygiene in preventing SSTI. Interventions to increase swabbing should be included as part of a wider package of injecting hygiene education, particularly in light of associations with receptive and/or distributive syringe sharing.